2010
DOI: 10.2478/v10125-010-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mitochondrial DNA of unionid bivalves (Mollusca: Bivalvia: Unionidae). I. Detection and characteristics of doubly uniparental inheritance (DUI) of unionid mitochondrial DNA

Abstract: Doubly Uniparental Inheritance (DUI), a peculiar way of inheritance of mitochondrial DNA in animals, has been detected in seven families of marine and freshwater bivalves, including Unionidae. DUI involves two independently inherited mitochondrial genomes: maternal (F genome) and paternal (M genome), which show different tissue localisation and wide genetic variation. F genomes occur in somatic tissues of both sexes and are inherited maternally (Strict Maternal Inheritance, SMI). M genomes are located in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 134 publications
(314 reference statements)
2
39
0
1
Order By: Relevance
“…Specimens from the Italian lake cluster in clade 2. Sequences of specimens identified as U. pictorum by Soroka (2010) all clustered in clade 3 together with our own material of U. pictorum. Average divergence within the U. pictorum clade was 0.3% (max: 1%), average divergence within the U. mancus clade was 0.5% (max 1.3%), minimum distance between U. mancus and U. pictorum was 2.9%.…”
Section: Resultsmentioning
confidence: 70%
“…Specimens from the Italian lake cluster in clade 2. Sequences of specimens identified as U. pictorum by Soroka (2010) all clustered in clade 3 together with our own material of U. pictorum. Average divergence within the U. pictorum clade was 0.3% (max: 1%), average divergence within the U. mancus clade was 0.5% (max 1.3%), minimum distance between U. mancus and U. pictorum was 2.9%.…”
Section: Resultsmentioning
confidence: 70%
“…Specimens of S. woodiana from 5 analysed Polish populations had identical sequences of the mitochondrial cox1 gene fragment. They did not differ from those of individuals from other populations in Poland (Soroka, 2010), Hungary, Italy, and Ukraine (Tab. 1, Fig.…”
Section: Discussionmentioning
confidence: 89%
“…So far, studies of European species of Unionidae have revealed a low variation within the cox1 gene (less than 1%) in Unio gibbus, U. pictorum and U. tumidus, as well as Anodonta anatina (Källeresjö et al, 2005, Araujo et al 2009, Soroka 2008b, 2010. A higher intraspecific variation of the cox1 gene was reported for the gastropod Sadleriana fluminensis (3%) (Szarowska and Falniowski, 2013) and Potamilus species (2.6%) (Roe and Lydeard, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of DUI in this species was confirmed but only individual mitochondrial genes have been characterized (Soroka, 2010b). Here we present, sequenced for the first time, the complete sequences of both genomes, first such case in the genus Unio and second among European Unionidae after Anodonta anatina (Soroka & Burzynski, 2015.…”
Section: Introductionmentioning
confidence: 81%